1989
DOI: 10.2136/sssaj1989.03615995005300030029x
|View full text |Cite
|
Sign up to set email alerts
|

Texture, Climate, and Cultivation Effects on Soil Organic Matter Content in U.S. Grassland Soils

Abstract: Soil organic C content, a major source of system stability in agroecosystems, is controlled by many factors that have complex interactions. The purpose of this study was to evaluate the major controls over soil organic carbon content, and to predict regional patterns of carbon in range and cultivated soils. We obtained pedon and climate data for 500 rangeland and 300 cultivated soils in the U.S. Central Plains Grasslands, and statistically analyzed relationships between C and soil texture and climate. Regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

47
497
8
9

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 798 publications
(561 citation statements)
references
References 0 publications
47
497
8
9
Order By: Relevance
“…It is known from field measurements that SOC content tends to be higher when C mineralization rates are reduced, such as in soils with a high clay or clay plus silt content (Hassink 1994). Clay-rich soils often occur at sites with high P (Burke et al 1989), which is not indicated by the regression analysis, whereas the direct influence of texture is very clear (Fig. 5).…”
Section: Discussionmentioning
confidence: 95%
“…It is known from field measurements that SOC content tends to be higher when C mineralization rates are reduced, such as in soils with a high clay or clay plus silt content (Hassink 1994). Clay-rich soils often occur at sites with high P (Burke et al 1989), which is not indicated by the regression analysis, whereas the direct influence of texture is very clear (Fig. 5).…”
Section: Discussionmentioning
confidence: 95%
“…In South Africa, approximately 30% of all plants sold in traditional medicine markets grow in grasslands (Williams et al, 2000). Grasslands also sequester carbon as soil organic matter stored mostly below ground (Burke et al, 1989;Sala and Paruelo, 1997), reducing the amount of carbon in the atmosphere that contributes to climate change. One of the most valuable services provided by grasslands is that of water supply.…”
Section: Introductionmentioning
confidence: 99%
“…Paustian et al [1992] used CENTURY to study influences of organic amendments and N fertilization on SOM in long-term plots. A revised version of CENTURY was tested against a multiyear, multisite data set on plant production and soil C and N dynamics in several grassland ecosystems and then used to simulate the responses to general circulation model derived climate change [Ojima et We also present predictions from empirical regression models reported by Burke et al [1989] and Schimel et al [1994]. In a companion paper [Peng and Apps, this issue] we report use of the model to examine carbon dynamics along the BFTCS under different scenarios of climate change.…”
mentioning
confidence: 99%